On some methods and applications of ordered Banach spaces - Achille Basile (FedOAPress, 2014)
Spaces of infinite dimension have played an increasing role in the last four decades concerning their applications in models both for economics and for finance. The intertemporal allocation of resources, commodity differentiation, uncertainty, dynamics of the fundamental variables of financial markets, are some of the issues that can be properly captured by means of the mathematical techniques that are typical in such spaces. This collection contains some recent contributions in this area.
Keywords: 330; Asymmetric information; compact operators; Fefferman inequalities; embeddings; expectations equilibria; rational; c-fair allocations; ex-post core